Transfection of Kasumi-1 cells with a new type of polymer carriers loaded with miR-155 and antago-miR-155 - Klimenko, O V; Shtilman, M I (Cancer gene therapy, 2013)
Previous studies have demonstrated functional roles for microRNAs (miRNAs) in various aspects of normal and malignant hematopoiesis, including lineage commitment, differentiation, apoptosis and maturation. In vivo delivery of naked DNA, oligonucleotides and miRNAs is complicated by their low stability, rapid degradation and inefficient delivery into target cells. In our experiments, we used a new type of polymer carriers to monitor the effects of miR-155 and antago-miR-155 on the morphology and genetics of Kasumi-1 cells. We obtained platelet-like cells from leukemic cells, and detected the expression of platelet marker genes after transfection with antago-miR-155. Our findings suggest that administration of miR mimics or antago-miRs as therapeutic agents is a desirable goal for future treatment of hematologic malignancies and that polymer-based carriers for the delivery of miR mimics or antago-miRs may provide a solution to the challenges of standard miR delivery approaches.